Management of life-threatening anaphylactic shock induced by Ceftriaxone following negative intradermal skin test in an Intensive Care Unit of a peripheral district hospital: a case report - Bijukchhhe, Satish; Sanjel, Anup; Banjade, Prakash; Adhikari, Samikshya (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Ceftriaxone is frequently used in the treatment of infectious diseases. Ceftriaxone-induced anaphylactic reactions are rare. But once Anaphylaxis occurs, it is severe, quickly progressive, and potentially fatal. Case report: A 58-year-old female presented with abdominal pain for 3 days. Vital signs and physical exam were unremarkable. Investigation revealed an increase in total leukocyte count for which the patient was admitted to the ward and started on Ceftriaxone. After 5 minutes of IV ceftriaxone injection, the patient complained of difficulty in breathing, generalized body itching, and mild rash with hypotension and hypoxia. Following diagnosis of anaphylactic shock, immediate management with oxygen, injection Adrenaline, Hydrocortisone, Pheniramine maleate, IV crystalloid, and injection Noradrenaline infusion was given. The patient’s clinical condition improved. She was weaned off after 48 hours and discharged. Conclusion: Early recognition, timely action, vigilant supervision, and organized teamwork have a significant impact on patient outcomes for ceftriaxone-induced anaphylactic reactions.